Lung collagens perpetuate pulmonary fibrosis via CD204 and M2 macrophage activation. - Mirjam Stahl (Public Library of Science (PLoS), 2013)
Idiopathic pulmonary fibrosis is characterized by abundant collagen production and accumulation of alternatively activated macrophages (M2) in the lower respiratory tract. Mechanisms as to how alveolar macrophages are activated by collagen breakdown products are unknown. Alveolar macrophages were obtained by bronchoalveolar lavage from 30 patients with idiopathic pulmonary fibrosis (IPF) and 37 healthy donors (HD). Alveolar macrophages were cultured in the presence of collagen type I, III, IV and V monomers w/wo a neutralizing antibody against scavenger receptor I class A (CD204). Culture supernatants were assayed for the M2 markers CCL18, CCL2, and interleukin-1 receptor antagonist (IL-1ra) by ELISA. Furthermore, expression of phospho-Akt was measured using ELISA and expression of CD204 by RT-PCR and flow cytometry. Stimulation with collagen type I and III monomers significantly up-regulated CCL18, IL-1ra production of alveolar macrophages. Furthermore, expression of CCL2 and CD204 were up-regulated by collagen type I exposure. In addition, collagen type I stimulation increased pospho-Akt expression. Collagen type I effects were abrogated by neutralizing antiCD204 and a non-selective Phosphatidylinositide 3-kinase inhibitor (LY294002). Spontaneous CD204 expression of alveolar macrophages was significantly increased in patients with IPF. In conclusion, our findings demonstrate that monomeric collagen type I via CD204 induces phospho-Akt expression shifting alveolar macrophages to the profibrotic M2 type. Innate immune responses induced by collagen monomers might perpetuate pulmonary fibrosis.